Sistem Peringatan Dini Banjir Secara Real-Time Berbasis Web Menggunakan Arduino dan Ethernet - Satria, Dedi; Yana, Syaifuddin; Munadi, Rizal; Syahreza, Saumi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2017)
a b s t r a c tThe development of flood early warning technology has grown rapidly. The technology has led to an increase in technology in terms of communication and information. Internet of Things technology (IoTs) has provided a major influence on the development of early warning information system. In this article a protipe-based flood monitoring information system of Google Maps have been designed by integrating Ultrasonic sensors as the height of the detector, the Arduino Uno as a processor, U-Blox GPS modules Neo 6 m GSM module and as the sender of data is the height of the water and the coordinates to the station of the system informais flood. The design of the prototype produces information flood elevations along with location based Google Maps interface.Keywords:Flood, Arduino, Internet of Things Technology (IoTs), Ethernet a b s t r a kPengembangan teknologi peringatan dini banjir telah tumbuh dengan cepat. Teknologi tersebut telah mengarah kepada peningkatan di segi teknologi komunikasi dan informasi. Teknologi Internet of Things (IoTs) telah memberikan pengaruh besar terhadap perkembangan sistem informasi peringatan dini. Didalam artikel ini sebuah protipe sistem informasi monitoring banjir berbasis Google Maps telah dirancang dengan mengintegrasikan sensor ultrasonik sebagai pendeteksi ketinggian, Arduino Uno sebagai pemroses, modul GPS U-Blox Neo 6m dan modul GSM sebagai pengirim data ketinggian air dan koordinat ke stasion sistem informais banjir. Perancangan prototipe menghasilkan informasi ketinggian banjir beserta lokasinya berbasis antarmuka Google Maps.Kata Kunci: Banjir, Arduino, Internet of Things Technology (IoTs), Ethernet